A Snapshot of Public Finance Research from Immediately Prior to the Pandemic: IIPF 2020 - David R. Agrawal; Ronald B. Davies; Sara LaLumia; Nadine Riedel; Kimberley Ann Scharf (Center for Economic Studies and ifo Institute (CESifo), 2021)
As the COVID-19 pandemic has shaped public policies and government finances, it has also influenced the topics that public finance economists are researching. Because the 2020 International Institute of Public Finance (IIPF) Congress featured papers that were submitted prior to the start of the pandemic, the Congress allows us to reflect on the state of research prior to the pandemic's shock to both fiscal policies and our worldview. In this article, the Editors of International Tax and Public Finance (ITAX), reflect on interesting papers that were presented at this internationally representative conference in public economics. The exercise provides insight on where the field of public economics was heading prior to the pandemic and will provide a yardstick to see how the field evolves in the coming years.
Keywords: H10; H20; H30; H40; H50; H60; H70; H80; 330; public economics; public finance; taxation; expenditures